The Influence of Website Quality and Social Media Quality on Brand Image, with Brand Awareness and Electronic Word of Mouth Mediating (Case Study at Legend Coffee Yogyakarta) - Misbahul Anwar; Andrian; Rani Juniar Hartono (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this study is to compare the quality of websites and social media to brand image, using brand awareness and E-WOM as mediation factors. The exogenous factors in this study are website and social media quality; the endogenous variables are brand image; and the mediating variables are brand awareness and E-WOM. The Legend Coffee coffee shop is the focus of this study, with a sample size of 200 respondents. The study's subjects were Legend Coffee consumers. The data analysis approach used in this work is Structural Equation Modeling (SEM) utilizing AMOS 24 analytic tools. Based on the results of this study, it shows that website quality has a positive and significant effect on brand awareness, social media quality has a positive and significant effect on brand awareness, website quality does not have a positive and significant effect on brand image, social media quality has a positive and significant effect on brand image, brand awareness has a positive and significant effect on E-WOM, E-WOM has a positive and significant effect on image brand, as well as brand awareness and E-WOM mediate website quality and social media quality to brand image.